67.1k views
4 votes
Y = -3x + 6

Slope:

y-intercept:


y = 4/3x - 1

Slope:

y-intercept:


y = -1/5x + 3

Slope:

y-intercept:​

2 Answers

1 vote

Answer:

Explanation:

y= -3x +6
y=(4)/(3) x-1

slope: -3 slope=4/3x

y-intercept: (0,6) y-intercept:(0,-1)


y=-(1)/(5) x+3

slope: -1/5x

y-intercept: (0,3)

User Euther
by
5.4k points
3 votes

Answer:

Explanation:

y = mx + c

Slope = m

y-intercept = c

1) y = -3x + 6

Slope = -3

y-intercept = 6

2) y = 4/3 x - 1

Slope = 4/3

y-intercept = -1

3) y = -1/5x+3

Slope = -1/5

y-intercept = 3

User Furniture
by
5.8k points